The relationship between job characteristics and job satisfaction among employee at Pustaka Negeri Sarawak/ Khairuddin Kadir - Kadir, Khairuddin (2016)
This chapter one discusses the common knowledge of the research conducted. It has the background of study, research problems, research objectives, research questions, limitation of study, significance of study and the definition of terms. In this part, the researchers are responding as to why there is a need to conduct a research for the following matter.